Solve for a -6a+3=-3(2a-1)

Math
-6a+3=-3(2a-1)
Simplify -3(2a-1).
Tap for more steps…
Apply the distributive property.
-6a+3=-3(2a)-3⋅-1
Multiply.
Tap for more steps…
Multiply 2 by -3.
-6a+3=-6a-3⋅-1
Multiply -3 by -1.
-6a+3=-6a+3
-6a+3=-6a+3
-6a+3=-6a+3
Move all terms containing a to the left side of the equation.
Tap for more steps…
Add 6a to both sides of the equation.
-6a+3+6a=3
Combine the opposite terms in -6a+3+6a.
Tap for more steps…
Add -6a and 6a.
0+3=3
Add 0 and 3.
3=3
3=3
3=3
Since 3=3, the equation will always be true for any value of a.
All real numbers
The result can be shown in multiple forms.
All real numbers
Interval Notation:
(-∞,∞)
Solve for a -6a+3=-3(2a-1)

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top